Heat storage material and producing method thereof
A heat storage material with hydrophobic silica aerogel supporting latent heat storage material addresses leakage issues and manufacturing challenges, ensuring easy production and cost-effectiveness.
Patent Information
- Application Number
- JP2023101426
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-09
AI Technical Summary
Existing methods for manufacturing latent heat storage materials face challenges such as complexity, low productivity, high cost, and leakage due to insufficient support in hydrophilic porous silica, requiring additional resin coating.
A heat storage material comprising hydrophobic silica aerogel with high oil absorption supporting a latent heat storage material up to 60% by volume, characterized by specific properties like oil absorption, median diameter, specific surface area, and pore structure, is produced by kneading the latent heat storage material into the aerogel.
The solution effectively prevents leakage of the latent heat storage material during phase change, enhancing manufacturability and reducing costs by simplifying the process.
Smart Images

Figure 2025001768000001 
Figure 2025001768000002 
Figure 2025001768000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat storage material and a method for producing the same, and more particularly to a heat storage material which is easy to produce and does not ooze out when the latent heat storage material is in a liquid phase, and a method for producing the same. [Background technology]
[0002] In recent years, there has been a demand for energy conservation by effectively utilizing thermal energy. As an effective method, latent heat storage materials (e.g., aliphatic hydrocarbon compounds such as n-paraffin, higher alcohols, inorganic salts, etc.) that store heat by utilizing latent heat accompanying the phase change of a substance have been considered. Since latent heat storage materials utilize the latent heat due to the phase change between liquid and solid of a phase change substance, there is a problem that the liquid seeps out when it becomes liquid. As a method for solving this, a method of microencapsulating the latent heat storage material by encapsulating it in a shell (see Patent Document 1) and a method of impregnating a porous silica powder with the latent heat storage material and then coating it with an organic resin (see Patent Document 2) have been proposed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-86517 [Patent Document 2] JP 2009-203352 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the method of microencapsulating the latent heat storage material requires a complicated process, and there are problems in terms of productivity and cost. In addition, in the method of impregnating the latent heat storage material into the porous silica powder, since the surface of the porous silica is hydrophilic and has a low oil absorption, if the latent heat storage material is impregnated without seeping out, only a small amount of the latent heat storage material can be added. Even if the surface of the porous silica is treated to be hydrophobic to solve this problem, the amount of the latent heat storage material added is insufficient because of the low oil absorption. Therefore, in order to sufficiently add the latent heat storage material to the porous silica, a process of coating with an organic resin is required, which has problems in terms of productivity and cost. Therefore, the object is to provide a heat storage material that is easy to manufacture and does not seep out when the phase change material becomes a liquid phase state. [Means for solving the problem]
[0005] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that a heat storage material that does not bleed out can be obtained by supporting a liquid latent heat storage material on a hydrophobic silica aerogel having a high oil absorption of 400 to 800 ml / 100 g at 60 volume % or less of the oil absorption. They have also found that a heat storage material that does not bleed out can be easily produced by simply kneading and supporting the latent heat storage material on the hydrophobic silica aerogel.
[0006] That is, the heat storage material of the present invention is a heat storage material containing a latent heat storage material and a hydrophobic silica aerogel having an oil absorption of 400 to 800 ml / 100 g as determined by a refined linseed oil method, and the latent heat storage material is supported in a liquid state at 60 volume % or less relative to the oil absorption of the hydrophobic silica aerogel. In the thermal storage material of the present invention, the hydrophobic silica aerogel has a volume-based median diameter measured by a Coulter counter method of 1 to 200 μm and a specific surface area measured by a BET method of 350 to 1000 m. 2 It is preferable that the peak values of the pore volume and pore radius measured by the BJH method are 1 to 6 ml / g and 3 to 40 nm, respectively. In the heat storage material of the present invention, the hydrophobic silica aerogel preferably has an average circularity of 0.8 or more as measured by an image analysis method. In the heat storage material of the present invention, the hydrophobic silica aerogel preferably has an M value of 20-60. In the heat storage material of the present invention, the latent heat storage material is preferably n-paraffin. The present invention also provides a method for producing a heat storage material, which includes a latent heat storage material and a hydrophobic silica aerogel having an oil absorption of 400 to 800 ml / 100 g as determined by a refined linseed oil method, and includes kneading the hydrophobic silica aerogel with a liquid latent heat storage material having an oil absorption of 60% by volume or less of the hydrophobic silica aerogel, thereby supporting the latent heat storage material in the pores of the hydrophobic silica aerogel. Effect of the Invention
[0007] The heat storage material of the present invention can prevent seepage of the phase-change substance when it becomes liquid by supporting the latent heat storage material in the pores of the hydrophobic silica aerogel having a high oil absorption. The method for producing a heat storage material of the present invention comprises kneading a hydrophobic silica aerogel having a high oil absorption with a liquid latent heat storage material in an amount of 60 volume % or less of the oil absorption of the hydrophobic silica aerogel, thereby making it possible to support the latent heat storage material in the pores of the hydrophobic silica aerogel and easily produce a heat storage material that does not bleed out. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The following embodiments are merely examples of the present invention, and the present invention is not limited to these embodiments. The present invention will be described in detail below. [Heat storage material] The heat storage material of the present invention contains a latent heat storage material and a hydrophobic silica aerogel having an oil absorption of 400 to 800 ml / 100 g as determined by a refined linseed oil method, and the content of the liquid state of the latent heat storage material is 60 vol % or less relative to the oil absorption of the hydrophobic silica aerogel.
[0009] <Hydrophobic silica aerogel> The hydrophobic silica aerogel (hereinafter also simply referred to as "silica aerogel") contained in the heat storage material of the present invention may be a known one, and for example, one produced by the method described in JP 2018-177620 A can be used. Preferred properties of the silica aerogel used in the present invention are described below.
[0010] (Oil absorption amount) The oil absorption of the silica aerogel used in the present invention is 400mL / 100g or more and 800mL / 100g or less. 500mL / 100g or more is more preferable. When the oil absorption is within the above range, the latent heat storage material can be supported without exuding. When the oil absorption is less than the lower limit, the amount of latent heat storage material that can be supported is small, and the effect of suppressing exudation cannot be obtained. When the oil absorption exceeds the upper limit, exudation due to cracking tends to occur easily. The oil absorption amount is a value measured by the method described in JIS K5101-13-1 "Refined linseed oil method."
[0011] (Median diameter) The silica aerogel used in the present invention is not particularly limited in terms of the median diameter in the particle size distribution of volume frequency by the Coulter counter method (hereinafter, may be simply referred to as "median diameter"), but is preferably in the range of 1 to 30 μm. When the median diameter of the silica aerogel is in this range, a heat storage material that is easy to handle can be obtained. The median diameter is particularly preferably in the range of 3 to 20 μm.
[0012] (specific surface area) In the present invention, the specific surface area of the silica aerogel measured by the BET method (BET specific surface area) is preferably 350 to 1000 m 2 / g, and more preferably 400 to 850 m 2 When the BET specific surface area is within this range, it is possible to provide a heat storage material that does not exude, which is preferable. Here, the specific surface area measured by the BET method is a value obtained by drying a sample to be measured at a temperature of 200°C for 3 hours or more under a vacuum of 1 kPa or less, and then obtaining an adsorption isotherm only on the nitrogen adsorption side at liquid nitrogen temperature, and analyzing the resulting value by the BET method.
[0013] (Pore volume) The silica aerogel used in the present invention preferably has a pore volume of 3 to 6 mL / g. The lower limit is more preferably 3.5 mL / g or more, particularly 4 mL / g or more. The upper limit is more preferably 6 mL / g or less. It is preferable that the pore volume is within this range, since it exhibits an excellent effect in supporting the latent heat storage material. If the pore volume is smaller than this range, the voids become smaller, the amount of the latent heat storage material supported decreases, and exudation tends to occur easily. If the pore volume is larger than this range, exudation due to cracking tends to occur easily. The pore volume was obtained by obtaining an adsorption isotherm in the same manner as in the above-mentioned BET specific surface area measurement, and analyzing it by the BJH method (Barrett, EP; Joyner, LG; Halenda, PP, J. Am. Chem. Soc. 73, 373 (1951) (hereinafter, sometimes referred to as "BJH pore volume"). The pores measured by this method are pores with a radius of 1 to 100 nm, and the integrated value of the volume of pores in this range is the pore volume in the present invention.
[0014] (Pore radius peak) The silica aerogel used in the present invention is recommended to have a pore radius peak of preferably 10 to 40 nm, more preferably 10 to 30 nm. The pore radius peak being sharply present in this range improves the filling property when used as a heat storage material, and an excellent heat storage material can be provided. In the present invention, the peak of the pore radius is determined from the cumulative pore volume (volume distribution curve) based on the logarithm of the pore radius, which is obtained by analyzing the adsorption isotherm on the adsorption side obtained in the same manner as described above using the BJH method.
[0015] (Average circularity) In the present invention, the particle shape of the silica aerogel is not particularly limited, but it is preferably spherical, and its average circularity is preferably 0.8 or more, particularly preferably 0.85 or more. As the average circularity is greater than 0.8 and closer to 1, the individual particles become closer to a true sphere and the number of aggregated particles decreases. Therefore, if the average circularity is high, the filling property is improved when used as a heat storage material, and an excellent heat storage effect is obtained. The "average circularity" is a value calculated by obtaining an SEM image by observing with a scanning electron microscope (SEM) at a magnification of 1000 times with secondary electron detection and low acceleration voltage (1 kV to 3 kV), determining the value C (circularity) defined by the following formula (1) for each particle (image analysis), and calculating the arithmetic mean value of this circularity C for 2000 or more particles (image analysis method). At this time, a particle group forming one aggregate particle is counted as one particle. C=4πS / L 2 (1) In the above formula (1), S represents the area that the particle occupies in the image (projected area), and L represents the length of the outer periphery of the particle in the image (perimeter).
[0016] (M value) The silica aerogel is hydrophobic. Here, whether it is hydrophobic or not can be confirmed by the following method. That is, 25 ml of water is poured into a 50 ml glass sample bottle, 0.1 g of the silica aerogel to be tested is added, and the mixture is thoroughly shaken. After that, the silica aerogel can be confirmed to be entirely suspended in the water without being dispersed. The degree of hydrophobicity of the silica aerogel can be measured by the M value. The method for measuring the M value is as follows. 0.2 g of silica aerogel is added to 50 mL of water in a 250 mL beaker, and methanol is gradually added dropwise from a burette. During this process, the solution in the beaker is constantly stirred with a magnetic stirrer. The end point is when the entire amount of the added silica aerogel is suspended in the liquid, and the volume percentage (%) of methanol in the liquid mixture in the beaker at the end point is the M value. The M value, which is an index of hydrophobicity of the silica aerogel, is preferably 20 to 60, and more preferably 30 to 50. When the M value is within this range, it is possible to obtain a heat storage material that does not exude.
[0017] (Silylation) In the silica aerogel having the above M value, a specific example of a form in which hydrophobicity is imparted is a form in which an organic silyl group is introduced to the surface by treatment with a silylating agent. The organic silyl group is preferably a trimethylsilyl group, since it is likely to fall within the above-mentioned M value range. Specific examples of the silylating agent include chlorosilanes such as chlorotrimethylsilane, dichlorodimethylsilane, trichloromethylsilane, etc., alkoxysilanes such as monomethyltrimethoxysilane, monomethyltriethoxysilane, etc., silazanes such as hexamethyldisilazane, hexamethylcyclotrisilazane, etc., siloxanes such as hexamethylsiloxane, octamethyltrisiloxane, etc., and cyclic siloxanes such as siloxane octamethylcyclotetrasilazane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, etc. Among them, chlorotrimethylsilane, dichlorodimethylsilane, trichloromethylsilane, octamethylcyclotetrasiloxane, hexamethyldisilazane, and hexamethyldisiloxane are particularly preferred because they are easy to control the M value within the above-mentioned range. In general, the silylating agent reacts with the silanol groups of the silica aerogel to introduce corresponding hydrophobic groups onto the surface of the silica aerogel.
[0018] <Latent heat storage material> The latent heat storage material used in the heat storage material of the present invention is a substance that can store latent heat by undergoing a phase change between liquid and solid.
[0019] As the latent heat storage material used in the present invention, a hydrophobic latent heat storage material that is compatible with the hydrophobic surface is preferable because it is supported in the pores of the hydrophobic silica aerogel. In addition, a paraffin-based hydrocarbon compound that is low in corrosiveness, does not have a drawback in stability such as denaturation and deterioration due to repeated heat storage and heat release cycles, and can control the melting point to an operating temperature range according to the application by selecting the carbon number or the carbon number composition as a mixture is preferable. A specific paraffin-based hydrocarbon compound can be n-paraffin. n-Paraffin is a general term for saturated hydrocarbons that have no double bonds in a straight chain, and since the melting point differs depending on the carbon number, heat storage at various temperatures is possible. As the n-paraffin that can be used in the present invention, n-paraffins with 8 to 40 carbon atoms that have sufficient latent heat in a temperature range suitable for heat retention and cold retention applications are preferable, and examples thereof include tetradecane (carbon number 14), hexadecane (carbon number 16), and heptadecane (carbon number 17). The freezing point of n-paraffin is −50 to 80° C. depending on the carbon number, and can cover a wide temperature range according to the carbon number. The n-paraffin may be one having a single carbon number or two or more types having different carbon numbers may be used in combination.
[0020] (Content) The ratio of the latent heat storage material in the heat storage material of the present invention is in the range of 60% by volume or less in a liquid state relative to the oil absorption amount of the silica aerogel. More preferably, it is in the range of 10% by volume or more and 60% by volume or less. If the ratio of the latent heat storage material exceeds 60% by volume, it is not preferable because the volume expansion caused by the phase change of the latent heat storage material from solid to liquid causes the latent heat storage material to bleed out of the pores of the silica aerogel.
[0021] [Method of manufacturing heat storage material] The heat storage material of the present invention can be produced by uniformly kneading the hydrophobic silica aerogel with a molten latent heat storage material. The kneading is performed in the same manner as the method described in JIS K5101-13-1 "Refined linseed oil method", by dropping the molten latent heat storage material into the hydrophobic silica aerogel little by little and kneading it with a palette knife. At this time, kneading is performed until there are no lumps of 0.5 mm or more when visually observed and the mixture is uniform.
[0022] The form of use of the present heat storage material is not particularly limited. For example, the present heat storage material may be used by mixing with other materials such as paint, ink, adhesive, resin, and inorganic material. EXAMPLES
[0023] EXAMPLES In the following, examples are shown to specifically explain the present invention, but the present invention is not limited to these examples.
[0024] <Method of manufacturing silica aerogel> The hydrophobic silica aerogel has a surface modified with trimethylsilyl groups and was produced according to the method described in Example 1 of JP 2018-177620 A. The manufacturing procedure of the silica aerogel used in the examples is described below. (S1: Aqueous silica sol preparation process) While stirring 100 g of sulfuric acid with a stirring blade, 100 g of sodium silicate was gradually added to prepare an aqueous silica sol having a pH of 3.0. (S2: Emulsion formation process) 108 g of the aqueous silica sol prepared in S1 was taken, 160 g of heptane was added, and 1.6 g of sorbitan monooleate was added. This solution was stirred for 3 minutes at 5000 rpm using a homogenizer (IKA, T25BS1) to form a W / O emulsion. (S3: gelation process) The resulting emulsion was gelled at 70° C. for 5 hours while being stirred with a stirring blade. (S4:W phase separation step) 40 g of isopropyl alcohol and 60 g of ion-exchanged water were added, and the mixture was stirred with a stirring blade to separate the O phase and the W phase. (S5: gelled body maturation process) Subsequently, 1.60 g of a 0.5 mol / L aqueous solution of sodium hydroxide was added. At this time, the pH of the W phase was 5.0. The gel was aged at 70° C. for 2.5 hours. (S5-2: W phase recovery process) The O phase was removed by decantation, and the W phase was recovered. (S6: Silylation treatment process) 10 g of 35% hydrochloric acid and 12 g of hexamethyldisiloxane were added to the obtained W phase, and the mixture was kept in a water bath at 70° C. for 12 hours with stirring, thereby carrying out a silylation treatment. (S7: Gel body extraction process) After the silylation treatment, 7.14 g of 48% sodium hydroxide aqueous solution was added while stirring with a stirring blade to perform neutralization treatment. Next, 100 g of heptane was added to extract the gel, which was then washed twice with 100 g of ion-exchanged water. (S8: Gel body recovery process) The gel obtained after silylation was filtered using a suction filter. The gel was dried under vacuum pressure at 150°C for 16 hours or more to obtain a powder consisting of hydrophobic spherical silica aerogel. The physical properties of the obtained silica aerogel are shown in Table 1.
[0025] <Porous Silica> The following porous silica was used: Hydrophilic porous silica: "Toxil NP" from Oriental Silicas Corporation Hydrophobic porous silica: "Tokusil NP" was treated with silicone oil to give a hydrophobic surface according to the method described in Example 1 of JP 2020-147467 A. The experimental procedure is as follows. 400g of silica particles were placed in a 35L mixer container, and while stirring, nitrogen was supplied to create a nitrogen atmosphere in the container and heated to 270°C. The container was not sealed, but left open, and dimethyl silicone oil with a viscosity of 50cSt was heated to 100°C and sprayed using a two-fluid nozzle in an amount of 12% by mass relative to the silica particles of the base material. After spraying, the mixture was stirred for 1 hour while maintaining the above atmosphere and temperature to obtain silicone oil-treated silica particles. Various physical properties of the porous silica are shown in Table 1.
[0026] [Table 1]
[0027] <Evaluation method> The physical properties of the silica aerogel and the like were evaluated by the following methods.
[0028] (Measurement of average circularity) More than 2000 silica particles were observed at a magnification of 1000 times using an SEM (Hitachi High-Technologies S-5500, accelerating voltage 3.0 kV, secondary electron detection), and the SEM images were analyzed, and the average circularity was calculated according to the definition described above.
[0029] (Particle size distribution and median diameter measured using the Coulter counter method) 0.3 g of silica was added to 40 ml of ethanol, and dispersed for 5 minutes at 100 W output using an ultrasonic cleaner UT-105S manufactured by Sharp Manufacturing Co., Ltd. The dispersion was carried out using a 50 ml Labolan screw cap flask placed in a cleaning tank containing an appropriate amount of water. The obtained ethanol dispersion was measured using a Beckman Coulter, Inc. precision particle size distribution measuring device, Multisizer 3, with a 100 μm aperture tube. From the obtained particle size distribution, the median diameter with respect to the volume distribution was evaluated.
[0030] (Measurement of other physical properties) The BET specific surface area and the BJH pore volume were measured according to the above definitions using a BELSORP-max manufactured by BEL Japan Co., Ltd. The oil absorption was measured by the "refined linseed oil method" specified in JIS K5101-13-1.
[0031] <Method of manufacturing latent heat storage material> The latent heat storage materials used were n-paraffin (melting point 48 to 50°C, density 0.90 g / mL) and heptadecane (melting point 22°C, density 0.78 g / mL) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0032] Example 1 (1) 2.0 g of silica aerogel was weighed out onto a glass plate, and molten n-paraffin was added dropwise in 4-5 drops until the weight reached 2.34 g, which was 20% by volume of the oil absorption, and the mixture was kneaded using a palette knife. The mixture was kneaded until no lumps of 0.5 mm or more were visible and the mixture was homogeneous. Here, the method for calculating the amount of latent heat storage material to be dropped will be described below. Dripping amount (g)=A×B / 100×C / 100×D A: Oil absorption of porous powder (mL / 100g) B: Weight of porous powder (g) C: Loading amount relative to oil absorption (%) D: Density of latent heat storage material (g / mL) (2) The heat storage material was placed on a pre-weighed oil absorbent paper. The oil absorbent paper was then removed and weighed to confirm that the weight change was within 0.5%, confirming that paraffin was supported by the silica aerogel.
[0033] (Examples 2 to 8, Comparative Examples 1 to 8) A heat storage material was produced in the same manner as in Example 1, except that the porous powder, the latent heat storage material, and the amount of the material supported relative to the oil absorption in Example 1 were changed as shown in Table 2.
[0034] <Bleed-out test> A bleed-out test was carried out on the heat storage materials produced according to the examples and comparative examples. Oil-absorbent paper was laid on the bottom of a petri dish, and 2.0 g of silica aerogel supporting latent heat storage material was placed on top of it. The material was placed in a thermostatic chamber at 80°C and left for 2 hours while being occasionally stirred (once per 30 minutes). The oil-absorbent paper was then removed and weighed to evaluate the bleed-out of paraffin. The calculation method for the bleed-out rate of paraffin is shown below. If it was 0% or less, it was recorded as 0%. Bleed out rate (%) = (CB) / A x 100 A: Weight of latent heat storage material in latent heat storage material support grain (g) B: Weight of oil absorbent paper before test (g) C: Weight of oil-absorbing paper after test (g)
[0035] The evaluation results are shown below.
[0036] [Table 2]
[0037] [Table 3]
[0038] From the results of Table 2, the heat storage material of the present invention, which is an embodiment, supports 60 volume % or less of the latent heat storage material relative to the oil absorption, and does not exude. In contrast, Comparative Examples 1 to 3 and 5 to 7, which support a large amount of the latent heat storage material, have a high bleed-out rate, and the latent heat storage material exudes from the pores. In Comparative Examples 4 and 8, which use hydrophilic porous silica, the oil absorption of the porous silica is low, so the latent heat storage material exudes even when a small amount of the latent heat storage material is supported. Comparative Examples 5 and 9, which use hydrophobic porous silica, also have a low oil absorption, and exudation of the latent heat storage material occurs. Therefore, it is considered that by supporting the latent heat storage material on silica aerogel, since the oil absorption is higher than that of porous silica, more latent heat storage material can be supported than porous silica, and exudation is further suppressed.
Claims
1. A heat storage material comprising a latent heat storage material and a hydrophobic silica aerogel having an oil absorption of 400 to 800 ml / 100 g as measured by a refined linseed oil method, A heat storage material, characterized in that the latent heat storage material is supported in a liquid state in an amount of 60 volume % or less relative to the oil absorption amount of the hydrophobic silica aerogel.
2. The hydrophobic silica aerogel has a volume-based median diameter of 1 to 200 μm as measured by the Coulter counter method, and a specific surface area of 350 to 1000 m as measured by the BET method. 2 2. The heat storage material according to claim 1, wherein the peak values of the pore volume and pore radius measured by the BJH method are 1 to 6 ml / g and 3 to 40 nm, respectively.
3. The heat storage material according to claim 1 or 2, wherein the hydrophobic silica aerogel has an average circularity of 0.8 or more as determined by an image analysis method.
4. The heat storage material according to claim 1 or 2, wherein the hydrophobic silica aerogel has an M value of 20 to 60.
5. The heat storage material according to claim 1 or 2, wherein the latent heat storage material is n-paraffin.
6. A method for producing a heat storage material comprising a latent heat storage material and a hydrophobic silica aerogel having an oil absorption of 400 to 800 ml / 100 g by a refined linseed oil method, comprising the steps of: A method for producing a heat storage material, comprising kneading the hydrophobic silica aerogel with a liquid latent heat storage material that is 60 volume % or less of an oil absorption amount of the hydrophobic silica aerogel, thereby supporting the latent heat storage material in the pores of the hydrophobic silica aerogel.
Citation Information
Patent Citations
Method for producing granular heat storage material
JP2009203352A
Heat storage microcapsule, heat storage microcapsule dispersion, and manufacturing method of heat storage microcapsule
JP2022086517A